Between rites and rights : excision in women's experiential texts and human contexts - Zabus, Chantal J. (Stanford University Press, 2007)
Modern African women writers have introduced a new autobiographical discourse around their experience of excision that brings nuance to the female genital mutilation debate. Spanning pharaonic times through classical antiquity to the onset of the 21st century, this study shows how this experiential body of literature - encompassing English, Arabic, and French - goes far beyond such traditional topics as universalism and cultural relativism, by locating the female body as a site of liminality between European and African factions, subject and agent; consent and dissent; custom and human rights.